A novel regimen for pancreatic ductal adenocarcinoma targeting MEK, BCL-xL, and EGFR - Song Han; Gerik W. Tushoski-Alemán; Peiyi Zhang; Guangrong Zheng; Daohong Zhou; Zhiguang Huo; Jonathan Licht; Thomas J. George; Carmen Allegra; Jose G. Trevino; Steven J. Hughes (Neoplasia: An International Journal for Oncology Research)
Oncogenic KRAS signaling plays a critical role in pancreatic ductal adenocarcinoma (PDAC) biology. Recent studies indicate that the combination of MEK and BCL-xL inhibition is synthetically lethal and holds promise for some types of solid cancers, however, patient response was poorly observed in PDAC predominantly due to amplified EGFR signaling. Here, we leverage the advantage of the combinational treatment strategy and designed a triplet regimen targeting the comprehensive RAS activation networks through simultaneously blocking MEK/BCL-xL/EGFR. The cytotoxicity of trametinib (MEK inhibitor), DT2216 (BCL-xL degrader) and afatinib (pan-EGFR inhibitor) and their combination was tested in patient-derived, primary PDAC cells using a live cell imaging system. Patient-derived xenograft (PDX) model was employed for the evaluation of the therapeutic efficacy and safety of the combinational regimen. Targeted pathway cascades activities were analyzed using multiplex phosphor-immune assays. In vitro comparisons showed the addition of afatinib as a third agent was statistically superior compared to a doublet of trametinib+DT2216 in suppressing cell growth and inducing cell death in all cell lines tested. This triplet similarly demonstrated significant superiority over the doublet of MEK/BCL-xL inhibition in the in vivo murine model. The triplet regimen was well tolerated in vivo. Overall tumor growth rates were significantly reduced in doublet treatment compared to controls, and further reduced in the triplet treatment group. Pathway analysis revealed the addition of afatinib in triplet regimen further inhibited PI3K/AKT effectors of p90RSK, p70S6K, and GSK3α/β along with a secondary pathway of P38 MAPK. Our study identifies an important contribution of EGFR inhibition to elevate the response of PDAC, supporting a clinical assessment of this triplet combination in patients.